ECONOMIC AND TECHNOLOGICAL ASPECTS OF THE USE OF BIOGAS MIXTURES IN THE CONDITIONS OF INDUSTRIAL FECILITIES - Kovalenko, Victor; Artemchuk, Victor; Levchenko, Sergii; Bashliy, Sergii (Scientific Journal "Metallurgy", 2021)
The results of calculations of economic feasibility of using biogas technologies in industrial furnacesare presented. To assess the economic efficiency of biogas use in the existing industrialenterprises of the metallurgical industry of Ukraine and Zaporizhia region, in particular, the basiceconomic indicators of conversion of standard furnace equipment to biogas mixtures from differentderived sources are calculated. The method based on the proposed calculation and thealgorithm presented in work [1], the technical feasibility of using biogas as an alternative fuel forenergy supply of thermal and heating furnaces of these enterprises on the example of a realobject. It is established that the use of low-calorie fuel in energy equipment, taking into accountits quality indicators, it is advisable both separately and in combination with traditional energysources. Based on the analysis of the existing equipment of the object of study, it was concludedthat the most suitable in the foundry of PJSC «Zaporizhstal», whose energy efficiency canbe increased through the use of biogas technologies, include continuous annealing furnacesand conveyor recirculating molds. For these units, foundry production when converting them tobiogas fuel, it is necessary to implement the following technical measures: the former requirereplacement of burners to meet the conditions of constant temperature, although they may consumeeven crude crude biogas, and the latter require deep processing of the latter to improveits quality and caloric content. The calculation of economic efficiency of conversion of the furnaceequipment inherent in the metallurgical industry to low-calorie biogas fuel on the exampleof the foundry of PJSC «Zaporizhstal» is given. Calculations have shown that the annual economiceffect is 1.42 and 19.01 million UAH. Per year, respectively, this indicates the feasibilityof using biogas technologies in industry.